2012
DOI: 10.1002/14651858.cd008634.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions for reducing antipsychotic medication in care home residents

Abstract: Psychosocial interventions for reducing antipsychotic medication in care home residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…11 However, care planning that involves a variety of available pharmacological and nonpharmacological approaches can meet the needs of people with Alzheimer’s and improve their quality of life once they are in a nursing home. 1,12,13 …”
Section: Optimal Carementioning
confidence: 99%
“…11 However, care planning that involves a variety of available pharmacological and nonpharmacological approaches can meet the needs of people with Alzheimer’s and improve their quality of life once they are in a nursing home. 1,12,13 …”
Section: Optimal Carementioning
confidence: 99%
“…first approved and have been used to treat schizophrenia and bipolar disorders since the 1970s; they are also regularly prescribed in residential care facilities as pharmacological interventions to control BPSD, followed by the prescription of atypical agents in the 1990s 6 . This is so, despite their moderate efficacy, the availability of non-pharmacological alternatives 5 , and serious adverse events (e.g., falls, increased risk of mortality) associated with their use 7,8 . Evidence indicates that the use of atypical antipsychotics was increased by about 35% in Ontario 9 associated with about 750% substantial increase in cost between 1993 and 2002.…”
Section: Introductionmentioning
confidence: 99%
“…This review found evidence to suggest that interventions incorporating medication review aimed at PWD can successfully reduce psychotropic drug prescribing [22,23]. Whilst previous reviews have identified interventions to reduce psychotropic drug use and manage BPSD [27][28][29], to the best of the authors' knowledge, this is the first systematic review to consider medicines management interventions holistically in this patient population.…”
Section: Discussionmentioning
confidence: 92%